A pulsating Gaussian wave packet - De Castro, A. S. [UNESP]; Da Cruz, N. C. (IOP Publishing, 1999)
A pulsating Gaussian wave packet for the harmonic oscillator is explicitly constructed. The mechanism for that behaviour is pointed out. © 1999 IOP Publishing Ltd.